Sosialisasi Pengenalan Transaksi Riba yang Dilarang Secara Syariah bagi Ibu-Ibu Rumah Tangga - Raden Hebat Kurnia; Wina Sari Asmara (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This community service activity aims to provide a deeper understanding for housewives regarding the concept, risks, and prohibition of usurious (riba-based) transactions from the perspective of Islamic economics. The background of this activity arises from the low level of public knowledge, especially among housewives, in distinguishing between conventional interest-based systems and Islamic economic systems that emphasize justice, balance, and blessings in financial transactions. The implementation method employed a participatory approach through lectures, counseling sessions, and interactive discussions to enhance participants’ comprehension and engagement. The program took place in RT 12, Kampung Baru Village, Muara Tembesi District, Batang Hari Regency, and involved 20 participants from a local women’s religious study group. The results showed a significant improvement in participants’ understanding of the types and prohibitions of riba, as well as its negative impacts on social and economic life. Moreover, participants expressed greater awareness and commitment to applying Islamic economic principles in household financial management. Therefore, this activity contributes to strengthening community literacy in Islamic economics and promoting financial behavior aligned with Islamic values.